GROWTH RATE OF PRODUCTION, PRODUCTIVITY AND AREA OF PEPPER IN KERALA: A COMPARATIVE STUDY BETWEEN PRE AND POST GLOBALIZATION ERA - RATISH MON AV (The Journal of Research ANGRAU, 2025)
The present study has analyzed the growth performance of pepper in Kerala in terms of area, production, productivity and price for the past 50 years (1970-71 to 2019-20) and quantified the impact of productivity growth and area growth on production growth. The analysis was carried out for three periods: pre-globalization period (1970-71 to 1990-91), post-globalization period (1991-92 to 2019-20) and the overall period (1970-71 to 2019-20). There was a decelerating trend in the area and production of pepper in the pre-globalization period.  The rate of deceleration was high in production (7.5%) compared to that of area (6.8 %). However, productivity and real price have shown an increasing trend. The post-globalization period has shown a decelerating trend in the area, production,  productivity and real price. The rate of deceleration was high in productivity (7.3 %) when compared with area (1 %),  production (4.7 %) and price (0.1 %). The overall (50 years) trend has shown a deceleration in area, production and productivity of pepper. The rate of deceleration was high in production and productivity However, the real price has accelerated by 0.2 %  per year.The decomposition analysis has shown the contributing factors to the growth of pepper production in the state which has increased in the case of area, from pre globalisation to globalization era. However, productivity has shown a negative effect. The interaction effect has increased by 11.25 % in 50 years